Fabrication of combined 0-3 and 1-3 connectivities PZT/epoxy resin composites - W. Thamjaree (2018)
PZT/epoxy resin composites of combined 0-3 and 1-3 connectivities were fabricated, for the first time, using suction, dice and fill techniques. Two types of composites (PZT(m)/epoxy resin and PZT(sp)/epoxy resin) were produced using PZT powders prepared by mixed oxide and spray-drying methods. Physical, mechanical, dielectric and piezoelectric properties of the composites were examined. Generally, overall results between the two composites were found to be very similar (volumetric changes ∼ 34-37%, d33∼20.2-25.3 pC/N, Kp^sim;0.54-0.61). Higher density was found in PZT(sp)/epoxy resin, however, due to better packing of particles. Moreover, both PZT/epoxy resin composites exhibited very low acoustic impedance (Z∼4.12-4.84 Mrayls), which is very close to that of human tissue and water. Therefore, these new composites may be suitable for use in medical applications. © Springer-Verlag 2004.